Characterization of Electronic Properties of Two-dimensional Refractory Selenides and Tellurides. Issue 47 (20th July 2016) - Biswas, Chandan; Lara Saenz, Gustavo A.; Fadil, Dalal; Kaul, Anupama B.
ABSTRACT: Transition metal dichalcogenides (TMDs) are emerging among the potential alternatives to graphene. The monolayer of TMDs can easily be exfoliated mechanically and their electronic properties can also be tuned by controlling the number of layers. TMDs possess an advantage over graphene by controlling band gap magnitude appropriate for the electronic and optoelectronic applications. Here we show, mechanically exfoliated TMDs such as NbSe2 and MoTe2 exhibit metallic and fluctuating conductance behavior respectively. Metallic conduction in NbSe2 was investigated under atmospheric conditions and compered with vacuum conditions. Furthermore, NbSe2 resistance was measured at low temperature up to 5.6 K. The above electronic investigations clearly demonstrate ohmic and fluctuating conduction in NbSe2 and MoTe2 respectively which could be applicable for electronic and optoelectronic devices.